The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/21548331.2020.1828888
|View full text |Cite
|
Sign up to set email alerts
|

The increasing importance of the novel Coronavirus

Abstract: Coronavirus disease 2019 (COVID-19) instigated by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has infected more`` than 20 million people, with more than more than 700000 deaths globally; and has been declared a pandemic. SARS-CoV-2 is recognized as the seventh coronavirus affecting Homo sapiens. The symptoms of COVID-19 consist of an elevated temperature, cough, diarrhea, and vomiting amongst others, whereas the transmission of SARS-CoV-2 is believed to arise via release of respiratory secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 83 publications
0
12
0
1
Order By: Relevance
“…A large number of SARS-CoV-2-infected patients exhibit a mild-to-moderate illness, about 5-10% of the infections occur serious and life-threatening cases, and the mortality rate is about 2% [37]. The number of new confirmed patients continues to increase, highlighting the importance of the development of rapid and effective therapeutic strategies by the design of new specific drugs or the repurposing of existing drugs [38]. Herein, we summarize the therapeutic effects of the existing drugs and substances from three aspects based on potential targets: virus entry, virus replication, and the immune system (Figure 2).…”
Section: Potential Therapeutic Strategiesmentioning
confidence: 99%
“…A large number of SARS-CoV-2-infected patients exhibit a mild-to-moderate illness, about 5-10% of the infections occur serious and life-threatening cases, and the mortality rate is about 2% [37]. The number of new confirmed patients continues to increase, highlighting the importance of the development of rapid and effective therapeutic strategies by the design of new specific drugs or the repurposing of existing drugs [38]. Herein, we summarize the therapeutic effects of the existing drugs and substances from three aspects based on potential targets: virus entry, virus replication, and the immune system (Figure 2).…”
Section: Potential Therapeutic Strategiesmentioning
confidence: 99%
“…Due to the anti-inflammatory properties of corticosteroids, it has been proposed that they could be used to treat or decrease COVID-19 infection complications [ 9 , 10 , 11 ]. Numerous studies revealed that the use of corticosteroids on non-cancer patients was associated with a 28-day reduction in mortality [ 9 ] and an increase in the number of days spent without the assistance of mechanical ventilation, particularly in patients who were critically ill [ 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Discovery of COVID-19 is grounded on the virological discovery by RT-PCR using hearties (nasopharynx, oropharynx), foam, feces, and also other suggestive attestations seen on casket radiographs and dynamic monitoring of seditious intercessors(e.g., cytokines). Utmost standard patterns observed on casket CT were ground-glass nebulosity, ill-de ned perimeters, smooth or irregular interlobular septal thickening, air bronchogram, crazy-paving pattern, and thickening of the conterminous pleura ( 13,14).…”
Section: Introductionmentioning
confidence: 99%